Assessing the impacts of donor support on Nigeria's health system: The global fund in perspective. Issue 243 (7th December 2021) - Kalu, Kenneth
Abstract: From 2003 to 2019, the Global Fund to Fight AIDS, Tuberculosis, and Malaria (the "Global Fund") disbursed a total of US2.3 billion in grants to Nigeria, mainly for the prevention and treatment of HIV/AIDS, tuberculosis, and malaria. This paper examines the impacts of the Global Fund's interventions on Nigeria's health system. Case study evidence shows that while the Global Fund has been successful in achieving its specific performance targets, its impacts on Nigeria's health system has been minimal at best. Major reasons for its negligible impacts on the country's health system include the Global Fund's ambivalent operational structure, little input from the host country in program design, excessive focus on fiduciary matters as opposed to public health interventions, as well as emphasis on parochial performance targets. Policy implications arising from this study include the need for domestic actors in Nigeria's health sector to have significant input in designing the Global Fund's projects in the country. In addition, the Global Fund's board and major donors should work collaboratively to refocus the institution to enhance its public health impacts.